2021
DOI: 10.3390/colloids5020033
|View full text |Cite
|
Sign up to set email alerts
|

On Concept of Hybrid in Colloid Sciences

Abstract: The concepts hybrid and hybridization are common in many scientific fields, as in the taxonomic parts of botany and zoology, in modern genetic, and in the quantum–mechanical theory of atomic–molecular orbitals, which are of foremost relevance in most aspects of modern chemistry. Years later, scientists applied the concept hybrid to colloids, if the particles’ domains are endowed with functionalities differing each from the other in nature and/or composition. For such denomination to be fully valid, the domains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 100 publications
(96 reference statements)
0
1
0
Order By: Relevance
“…For example, it has been observed that silver nanoparticles in cell suspension culture increase the content of several flavonoids, including hydroxybenzoic and hydroxycinnamic acids in the S149 bitter gourd. Moreover, total phenolic and flavonoid content of Caralluma tuberculata and Prunella vulgaris callus cultures showed increased after being stimulated by silver nanoparticle and silver-gold nanoparticles, respectively (Ali et al, 2019;La and Risuleo, 2021).…”
Section: Silver Nanoparticle As Elicitor In Plant Tissue Culturementioning
confidence: 99%
“…For example, it has been observed that silver nanoparticles in cell suspension culture increase the content of several flavonoids, including hydroxybenzoic and hydroxycinnamic acids in the S149 bitter gourd. Moreover, total phenolic and flavonoid content of Caralluma tuberculata and Prunella vulgaris callus cultures showed increased after being stimulated by silver nanoparticle and silver-gold nanoparticles, respectively (Ali et al, 2019;La and Risuleo, 2021).…”
Section: Silver Nanoparticle As Elicitor In Plant Tissue Culturementioning
confidence: 99%